Reviews of recent publications (Studies in 20th & 21st Century Literature, 1996)
Anderson, Stephanie. Le Discours Féminin de Marguerite Duras by Julia Lauer-Chéenne Booker, M. Keith. Literature and Domination: Sex, Knowledge, and Power in Modern Fiction by Frédérique Chevillot Chevillot, Frédérique. La Réouverture du texte by Susan Ireland Cixous, Hélène. Three Steps on the Ladder of Writing by Jeff Schneider Descombes, Vincent. The Barometer of Modern Reason: On the Philosophies of Current Events by André Pierre Colombat Holmgren, Beth. Women's Works in Stalin's Time: On Lidiia Chukovskaia and Nadezhda Mandelstam by Serafima Roll Lyotard, Jean François. Political Writings. Trans. Bill Readings and Kevin Paul Geiman by Ronald Bogue McPherson, Karen S. Incriminations: Guilty Women/Telling Stories by Colette Hall Melnick, Daniel C. Fullness of Dissonance. Modern Fiction and the Aesthetics of Music by Walter A. Strauss Scatton, Linda Hart. Mikhail Zoshchenko: Evolution of a Writer by Eric Lozowy Sollers, Philippe. Watteau in Venice by T. Douglas Doyle Steele, Cynthia. Politics, Gender, and the Mexican Novel, 1968-1988: Beyond the Pyramid by Jill S. Kuhnheim Webb, Barbara J. Myth and History in Caribbean Fiction. Alejo Carpentier, Wilson Harris and Eduard Glissant by Nicasio Urbina
Keywords: Stephanie Anderson; Le Discours Féminin de Marguerite Duras; Julia Lauer-Chéenne; M. Keith Booker; Literature and Domination: Sex Knowledge and Power in Modern Fiction; Frédérique Chevillot; La Réouverture du texte; Susan Ireland; Hélène Cixous; Three Steps on the Ladder of Writing; Jeff Schneider; Vincent Descombes; The Barometer of Modern Reason: On the Philosophies of Current Events; André Pierre Colombat; Beth Holmgren; Women& #x27; s Works in Stalin& #x27; s Time: On Lidiia Chukovskaia and Nadezhda Mandelstam; Serafima Roll; Jean François Lyotard; Political Writings; Bill Readings; Kevin Paul Geiman; Ronald Bogue; Karen S. McPherson; Incriminations: Guilty Women/Telling Stories; Colette Hall; Daniel C. Melnick; Fullness of Dissonance. Modern Fiction and the Aesthetics of Music; Walter A. Strauss; Linda Hart Scatton; Mikhail Zoshchenko: Evolution of a Writer; Eric Lozowy; Philippe Sollers; Watteau in Venice; T. Douglas Doyle; Cynthia Steele; Politics Gender and the Mexican Novel 1968-1988: Beyond the Pyramid; Jill S. Kuhnheim; Barbara J. Webb; Myth and History in Caribbean Fiction. Alejo Carpentier Wilson Harris Eduard Glissant; Nicasio Urbina